Analisa Kesenjangan Prevalensi Stunting Antar Kawasan di Indonesia Serta Faktor yang Mempengaruhinya - Lumbantoru, Melyana; Susanti, Hera (Jurnal Kebijakan Ekonomi, 2014)
Stunting is an indicator for chronic nutritional status that can provide a picture of overall socio-economic disruption in the past, starting from six months old infant and continue until the age of 18 years and can not be corrected again. The study concluded that infant growth monitoring, access to sanitation, health budget allocation per capita, income per capita and female literacy rate are significantiy reducing the occurrence of stunting. While the Theil index shows that the number of stunting is increasingly dispersed throughout Indonesia. At the regional level, the total disparity for stunting tends to decrease. In 2007, 2010 and 2013 the disparity between regions higher than within region, and the highest stunting disparity came from Sulawesi region.